Production of Composites for Future Application in Tendon/Ligament Repair - Joana Rita Lopes Ribeiro Nunes (2020)
Tendon and ligament injuries are among the most common and debilitating health problems affecting the adult population worldwide. Current treatments, surgical repair or grafts, have shown limited success. Driven by this market demand, several biological and non-degradable synthetic scaffolds have been developed but they fail in the long-term due to lack of implant integration or mechanical performance. The described shortcomings could be overcome through the use of biodegradable materials. However, their poor mechanical properties restrict their use in these load-bearing applications. The aim of this project is the development of biodegradable composite fibers, through the association of a reinforcing material into biocompatible and biodegradable polymers, to be used in the future in scaffolds with the required mechanical and biological performance for tendon/ligament repair.